Identification of mutations in theMYO9Agene in patients with congenital myasthenic syndrome - Emily O’Connor; Ana Töpf; Juliane S. Müller; Dan Cox; Teresinha Evangelista; J. Colomer; Angela Abicht; Jan Senderek; Oswald Hasselmann; Ahmet Yaramış; Steven H. Laval; Hanns Lochmüller (2016)
Congenital myasthenic syndromes are a group of rare and genetically heterogenous disorders resulting from defects in the structure and function of the neuromuscular junction. Patients with congenital myasthenic syndrome exhibit fatigable muscle weakness with a variety of accompanying phenotypes depending on the protein affected. A cohort of patients with a clinical diagnosis of congenital myasthenic syndrome that lacked a genetic diagnosis underwent whole exome sequencing in order to identify genetic causation. Missense biallelic mutations in the MYO9A gene, encoding an unconventional myosin, were identified in two unrelated families. Depletion of MYO9A in NSC-34 cells revealed a direct effect of MYO9A on neuronal branching and axon guidance. Morpholino-mediated knockdown of the two MYO9A orthologues in zebrafish, myo9aa/ab, demonstrated a requirement for MYO9A in the formation of the neuromuscular junction during development. The morphants displayed shortened and abnormally branched motor axons, lack of movement within the chorion and abnormal swimming in response to tactile stimulation. We therefore conclude that MYO9A deficiency may affect the presynaptic motor axon, manifesting in congenital myasthenic syndrome. These results highlight the involvement of unconventional myosins in motor axon functionality, as well as the need to look outside traditional neuromuscular junction-specific proteins for further congenital myasthenic syndrome candidate genes. Congenital myasthenic syndromes result from defects in the neuromuscular junction. Using whole exome sequencing, O'Connor et al. identify mutations in a novel candidate gene, MYO9A, which encodes an unconventional myosin. They provide preliminary evidence that MYO9A contributes to formation of the neuromuscular junction via effects on the presynaptic motor axon.